PRESERVASI BUDAYA OTOMOTIF MELALUI MUSEUM SEJARAH DI KEMAYORAN, JAKARTA - Putra, Samuel Losan; Hadiwono, Alvin (Jurusan Arsitektur dan Perencanaan, 2025)
The Kemayoran area has a unique history and culture. The automotive culture, with its history in Kemayoran, is a hidden aspect that has left a significant impression on automotive enthusiasts in this century, which is gradually being forgotten as interest in automotive activities among the residents of Kemayoran declines. This journal aims to explore how architectural science can be used to preserve and potentially revive automotive culture and interest in Kemayoran. With the understanding of the phrase